Characterizations and accurate computations for tridiagonal Toeplitz matrices. Issue 19 (16th December 2022) - Delgado, Jorge; Orera, Héctor; Peña, J. M.
ABSTRACT: Tridiagonal Toeplitz P -matrices, M -matrices and totally positive matrices are characterized. For some classes of tridiagonal matrices and tridiagonal Toeplitz matrices, it is shown that many algebraic computations can be performed with high relative accuracy.